Bacterial Composition and Diversity in Breast Milk Samples from Mothers Living in Taiwan and Mainland China - Li, Shiao-Wen; Watanabe, Koichi; Hsu, Chih-Chieh; Chao, Shiou-Huei; Yang, Zheng-Hua; Lin, Yan-Jun; Chen, Chun-Chiang; Cao, Yong-Mei; Huang, Hsuan-Cheng; Chang, Chuan-Hsiung; Tsai, Ying-Chieh (Frontiers in Microbiology, 2017)
Human breast milk is widely recognized as the best source of nutrients for healthy growth and development of infants; it contains a diverse microbiota. Here, we characterized the diversity of the microbiota in the breast milk of East Asian women and assessed whether delivery mode influenced the microbiota in the milk of healthy breast-feeding mothers. We profiled the microbiota in breast milk samples collected from 133 healthy mothers in Taiwan and in six regions of mainland China (Central, East, North, Northeast, South, and Southwest China) by using 16S rRNA pyrosequencing. Lactation stage (months postpartum when the milk sample was collected) and maternal body mass index did not influence the breast milk microbiota. Bacterial composition at the family level differed significantly among samples from the seven geographical regions. The five most predominant bacterial families were Streptococcaceae (mean relative abundance: 24.4%), Pseudomonadaceae (14.0%), Staphylococcaceae (12.2%), Lactobacillaceae (6.2%), and Oxalobacteraceae (4.8%). The microbial profiles were classified into three clusters, driven by Staphylococcaceae (abundance in Cluster 1: 42.1%), Streptococcaceae (Cluster 2: 48.5%), or Pseudomonadaceae (Cluster 3: 26.5%). Microbial network analysis at the genus level revealed that the abundances of the Gram-positive Staphylococcus, Streptococcus, and Rothia were negatively correlated with those of the Gram-negative Acinetobacter, Bacteroides, Halomonas, Herbaspirillum, and Pseudomonas. Milk from mothers who had undergone Caesarian section (C-section group) had a significantly higher abundance of Lactobacillus (P < 0.05) and a higher number of unique unclassified operational taxonomic units (P < 0.001) than that from mothers who had undergone vaginal delivery (vaginal group). These findings revealed that (i) geographic differences in the microbial profiles were found in breast milk from mothers living in Taiwan and mainland China, (ii) the predominant bacterial families Streptococcaceae, Staphylococcaceae, and Pseudomonadaceae were key components for forming three respective clusters, and (iii) a significantly greater number of unique OTUs was found in the breast milk from mothers who had undergone C-section than from those who had delivered vaginally.